PANETTE Sebuah Sistem Sibaliparri Dalam Keluarga Mandar - Chuduriah Sahabuddin (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2013)
This study aims to reveal the existence of the community as well as in the village of Karama Panette Polewali Mandar. The study was conducted in the village of Karama District of Tinambung sub Polewali Mandar, who inhabit this village is that the majority of the population earn as fishing, weaving and fish traders. The relationship between the three very closely, where the head of the family works as a fisherman and a housewife role as panette. The targeted data collection is working population as panette. The data taken in this study, are qualitative. Data were collected by in-depth interviews and observation . The results showed that the village of Karama is one panette community in Mandar. It is based on the socio-cultural and economic conditions that describe the social activities that tend to move in the field of weaving silk fabric. The socio-economic role played by women directly. This role is carried out on the basis of the value of philosophy sibali Parri as social and cultural values mandar.